2015
DOI: 10.1016/j.ibbai.2016.02.024
|View full text |Cite
|
Sign up to set email alerts
|

La utilización de las revistas electrónicas en la Universidad de León (España): hábitos de consumo y satisfacción de los investigadores

Abstract: , pp. 17-55 tareas investigadoras. La media de artículos anuales consultados es considerable y manifiesta diferencias claras entre las áreas de humanidades, ciencias sociales y ciencias de la naturaleza y la salud. El número de títulos de revistas consultados de modo regular por los investigadores de la Universidad de León se sitúa en una media cercana a 10, resultado que supera el umbral hallado en otros trabajos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
1
0
3
Order By: Relevance
“…Since the first download studies were carried out, it has been observed that the intensity of use is limited while the concentration of use is high. The greater availability of journals has resulted in a wide diversification of use, including titles that were not previously subscribed to on paper, and in many cases even prioritized over them This model has been sustained by the inertia resulting from the flattening of the publisher-library-user relationship due to the commercialization of all of the publisher's products academics have shown that researchers consult a small number of titles -rarely more than ten-and tend to opt for reputable titles (Rodríguez-Bravo; Alvite-Díez; Olea, 2015;King, 2002). The correspondence between the titles consulted and the journals chosen to communicate research is limited, an effect that occurs because academics read better-positioned journals than those in which they finally manage to publish their research (Rodríguez-Bravo; Alvite-Díez; Olea, 2015;Rodríguez-Bravo et al, 2013;King, 2002).…”
Section: Drawbacks Of the Big Deal: Constant Price Increases And Concentration Of Usementioning
confidence: 99%
“…Since the first download studies were carried out, it has been observed that the intensity of use is limited while the concentration of use is high. The greater availability of journals has resulted in a wide diversification of use, including titles that were not previously subscribed to on paper, and in many cases even prioritized over them This model has been sustained by the inertia resulting from the flattening of the publisher-library-user relationship due to the commercialization of all of the publisher's products academics have shown that researchers consult a small number of titles -rarely more than ten-and tend to opt for reputable titles (Rodríguez-Bravo; Alvite-Díez; Olea, 2015;King, 2002). The correspondence between the titles consulted and the journals chosen to communicate research is limited, an effect that occurs because academics read better-positioned journals than those in which they finally manage to publish their research (Rodríguez-Bravo; Alvite-Díez; Olea, 2015;Rodríguez-Bravo et al, 2013;King, 2002).…”
Section: Drawbacks Of the Big Deal: Constant Price Increases And Concentration Of Usementioning
confidence: 99%
“…La estadística descriptiva de los datos muestra una infrautilización de los recursos electrónicos subscritos por la UB. Pese a la importancia de los recursos electrónicos como elemento crítico en la investigación académica (Deng, 2010;Nicholas, Profile, Abrizah, Boukacem-Zeghmouri, y Clark, 2016) se confirma el bajo uso en el ámbito de las ciencias sociales y en las humanidades, como ya constató Rodríguez-Bravo et al (2015) en el estudio en la Universidad de León.…”
Section: Conclusiones Y Discusiónunclassified
“…Rosa Zaborras, Carina Rey Martín y Candela Ollé Castellà Del mismo modo, tanto en nuestro estudio como en el anteriormente citado (Rodríguez-Bravo et al, 2015), se observan algunos de los patrones de conducta descritos por en el análisis de los datos, como es el ratio de dispersión de los títulos de revista en la descarga de artículos, la coincidencia en el alto uso de paquetes de revistas electrónicas de grandes proveedores. Otros patrones (como el efecto rebote) no han podido ser contrastados, ya que los ficheros no disponían los datos necesarios para ello.…”
Section: # 180unclassified
“…La formación de investigadores, en la actualidad, es aprehendida desde diversas perspectivas. Ha sido abordada como: a) un proceso interdisciplinario y de búsqueda o contacto con la información (Rodriguez, Alvite y Olea, 2015;Salgado, Ortiz y Rogel, 2016); b) la consecuencia del ejercicio didáctico-tutorial (Dietz, 2014;Torrecilla, Cartagena, Crespo, Oyarzabal y Pérez, 2017); c) el producto de las políticas públicas (Rivas, 2004); d) una disposición organizacional (Gotuzzo, Gonzalez y Verdonck, 2010); e) el resultado de disposiciones personales (Giménez, Pedrazas, Medina y Dalmau, 2009; Moreno-Casbas, Fuentelsaz-Gallego, González-María y Gil de Miguel, 2010). Sin embargo, su comprensión como práctica social y sociodiscursiva aún está pendiente.…”
Section: Introductionunclassified